Laevomycetin release rate control in a silica-based composite system - Rugal, А.О.; Krupskaya, Т.V.; Тurov, V.V. (Reports of the National Academy of Sciences of Ukraine, 2018)
A composite system based on silica and laevomycetin is obtained, and the capability to control the antibiotic release rate by changing the silica surface coating with laevomycetin is shown. It is revealed that the method of impregnation is optimal due to its facility to regulate the desorption rate on a slow stage.